Discrimination of cathinone regioisomers, sold as 'legal highs', by Raman spectroscopy. Issue 7 (30th July 2013) - Christie, R.; Horan, E.; Fox, J.; O'Donnell, C.; Byrne, H. J.; McDermott, S.; Power, J.; Kavanagh, P.; Brandt, Simon D.
<x xml:space="preserve">Abstract</x> The discrimination of a cross section of cathinone regioisomers, sold as 'legal highs', using Raman spectroscopy, is reported here. Mephedrone and flephedrone were identified in 'legal high' products sold in Irish head shops, and their 2, 3 and 4‐isomers were synthesized as reference standards. The 3, 4‐methylenedioxy substituted cathinones, methylone, butylone and methylenedioxypyrovalerone (MDPV), were also identified in 'legal highs' and their 2, 3‐isomers were synthesized for comparison. In addition, alpha‐ and beta‐naphyrone were synthesized. Raman spectra of all the isomers were obtained using far‐red excitation (785 nm) and it was found possible to discriminate the isomers of each substituted cathinone. In addition, Raman spectra were also recorded for a number of head shop products and, by comparison with the reference standards, correct isomer assignment for 4‐mephedrone, 3‐flephedrone, 3, 4‐methylone, 3, 4‐butylone, 3, 4‐MDPV, alpha‐naphyrone and beta‐naphyrone was achieved, thus providing a non‐destructive, high‐throughput and minimal sample preparation technique for the discrimination of such drug isomers. Copyright © 2013 John Wiley & Sons, Ltd.